The coronation and campaigns of Alexander The Great (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
in this article, we will dwell on the process of coming to power of Alexander Makedonsky, who is recognized as the first Jahangir in history, having a special place in the history of the ancient world, and the wars that the activities of his military campaigns took especially to Central Asia